Identification of regulatory regions driving the expression of the Drosophila spalt complex at different developmental stages. - Barrio, R.; de Celis, J.F.; Bolshakov, S.; Kafatos, F.C. (Developmental Biology, 1999)
The zinc finger transcription factors Spalt and Spalt-related have been implicated in multiple developmental processes. In the wing they are regulated by the secreted protein Decapentaplegic and participate in the positioning of the wing veins. The function of Spalt has been also analyzed during tracheal development and embryonic segmentation. Here, we present the isolation and characterization of novel spalt/spalt-related alleles, which analysis indicates that these genes cannot substitute for each other in the developmental processes studied. The mutants present embryonic or pupal lethality, with phenotypes consistent with the loss of spalt function. We also present a detailed functional analysis of the DNA regions implicated in the regulation of these genes. This regulation is complex, integrating the information from both negative and positive regulators, and it is modular, with discrete fragments of DNA directing expression to discrete regions in embryonic and larval tissues.